Determinare le aree inondabili del fiume Ofanto per mezzo di un modello idraulico 1D/2D su base Lidar (GEOmedia, 2009)
Determination of Ofanto river flood risk areas through a 1D/2D Lidar hydraulic model The national emergency management services should lean on flood risk areas thematic maps in order to manage an eventual catastrophic event. The article, focused on the Ofanto river hydrographic basins, is a clear example of how an accurate knowledge of the terrain, obtained through the latest technological instruments as Lidar, could be important in these situations.